El Terraconcreto en Colombia: Apuntes para su historia - Vargas Rubiano, Hernando; Vargas Caicedo, Hernando (Dearq, 2007)
This paper considers the first recorded uses of soil-cement in rural house building in Colombia in 1942 after its promotion by Hernando Vargas Rubiano as architect with ICT (Instituto de Crédito Territorial). It studies the following developments in Colombia leading to the birth of the CINVA-RAM during the next decade.